2013
DOI: 10.1093/cercor/bht332
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Hypoxia, Hippocampal Atrophy, and Memory Impairment: Evidence of a Causal Sequence

Abstract: Neonates treated for acute respiratory failure experience episodes of hypoxia. The hippocampus, a structure essential for memory, is particularly vulnerable to such insults. Hence, some neonates undergoing treatment for acute respiratory failure might sustain bilateral hippocampal pathology early in life and memory problems later in childhood. We investigated this possibility in a cohort of 40 children who had been treated neonatally for acute respiratory failure but were free of overt neurological impairment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
86
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 45 publications
12
86
2
1
Order By: Relevance
“…However, hippocampus had a highest oxidative capacity which could be because of its higher metabolic demands, as previously observed [36,47]. Such effects made the hippocampus more vulnerable to the hypoxic insults, a result which is supported by previous studies [12,75]. The current study showed the positive impact of hypothermia to normalize the redox ratio under hypoxia, which implicated the protective role of hypothermia against oxidative insults.…”
Section: Discussionsupporting
confidence: 89%
“…However, hippocampus had a highest oxidative capacity which could be because of its higher metabolic demands, as previously observed [36,47]. Such effects made the hippocampus more vulnerable to the hypoxic insults, a result which is supported by previous studies [12,75]. The current study showed the positive impact of hypothermia to normalize the redox ratio under hypoxia, which implicated the protective role of hypothermia against oxidative insults.…”
Section: Discussionsupporting
confidence: 89%
“…Stepwise linear regression models revealed that the cohort's hippocampal volumes were predictive of some degree of memory impairment. In addition, the gestational age at the treatment was also predictive of hippocampal volumes losses: the younger the age, the greater the atrophy (Cooper, Gadian et al 2013), specially considering critical periods of development.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the relationship between hippocampal atrophy, memory impairments and neonatal anoxia has already been described (Bachevalier and Vargha-Khadem 2005;Cooper, Gadian et al 2013). In rodents, correlations between hippocampal atrophy and oxygen deprivation have been described in stroke models (Shrivastava, Chertoff et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the D&P test (10), we assessed the memory ability of 29 patients (mean age, 16:2; range, 9-33 y; 12 females), who had sustained (i) hypoxic/ischemic episodes in the neonatal and/or perinatal period (see Table 1 for details) and (ii) HV reduction greater than 10% of the mean HV of a group of 65 healthy controls (11). (One female patient suffered respiratory failure at age 12, which is thought to be the cause of the hippocampal damage.…”
Section: Methodsmentioning
confidence: 99%